Analysis of the Effect of Salary on the Participation of the Economically Active Population in Mexico (1993-2023) through an Econometric Model - Gálvez Rodríguez, Andrés; López-López José-de-Jesús; Báez Puerta, Tomás; Reyna Parra, Alfonso (Technium Social Sciences Journal, 2026)
This analysis investigates the impact of several macroeconomic variables on Mexico’s Economically Active Population (EAP), using an econometric model based on ordinary least squares (OLS). The EAP, as a variable linked to the labor market, depends on the minimum wage, Gross Domestic Product (GDP), inflation, interest rates, and foreign direct investment (FDI). The results are revealing: the predominant role of both the minimum wage and GDP on the EAP is evident. An increase in the minimum wage leads to an increase in the labor supply, and GDP reinforces the expansion of the labor force, as growth is boosted. However, certain factors act as obstacles: both inflation and high interest rates would limit hiring and, consequently, very likely decrease workers’ purchasing power. In contrast, foreign direct investment does not affect the EAP. This may be the result of a weak relationship between capital flows and short-term job creation. The model is excellent, with an R² of 0.972691, which explains 97.27% of the variation in the labor force participation rate. In short, increases in the minimum wage can stimulate job creation, provided these increases are accompanied by controls that are compatible with inflation and interest rates. Furthermore, creating a balanced economy is optimal for the relationship between foreign investment and employment, as it allows for sustainable and inclusive economic growth.